DIETARY DETERMINANTS OF HEMOGLOBIN LEVELS AMONG YOUNG ADULTS: EVIDENCE FROM A CROSS-SECTIONAL STUDY - ABUBAKAR; GUL-E-SABA CHAUDHRY; ZEENIA (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objectives: Nutrition plays a crucial role throughout all stages of life, but young adulthood is particularly significant for establishing healthy eating habits that can persist into the future. Globally, iron-deficiency anemia stands as the most prevalent cause of anemia, highlighting the importance of adequate iron intake during this formative period. This study aimed to (i) assess hemoglobin levels in male and female young adults and (ii) examine their association with dietary patterns. Methods: A cross-sectional study was conducted among adults (n=200). Data collection involved a structured questionnaire assessing dietary patterns, anthropometric measurements, and laboratory evaluation of hemoglobin levels. Results: A significant difference in the prevalence of overweight, obesity, and anemia was observed between the sexes. Among men, 88.9% were classified as overweight or obese (Class I), with 11.1% having mild anemia. In contrast, 66.7% of women were overweight, and 11.1% had severe anemia. Moreover, only 35% of women had normal hemoglobin levels, compared to 86% of men. The dietary analysis revealed an association between the intake of protein-rich foods – such as legumes, eggs, fish, and other animal sources – and the maintenance of healthy hemoglobin levels. The gender, food adequacy, and food diversity showed positive association through Kendall’s tau-b and Gamma test (0.522, 0.605, 0.437 and 0.849, 0.892, and 0.707, respectively) with p<0.001. Conversely, a significant negative association (−0.423, −0.365, −0.637, and −0.511, respectively) was observed between hemoglobin levels and factors such as body mass index and a family history of iron deficiency anemia across both genders. Conclusion: These findings underscore the critical need for robust electronic data collection systems within nutrition programs that are sensitive to gender-specific needs, thereby enabling the development of targeted and effective public health strategies to combat anemia and malnutrition in Pakistan.